Analysis Of Investment And Venture Capital On Profitability At Satria Jaya Cemplang Shop - Hurriyaturrohman, Hurriyaturrohman; Efendi, Yoga Ardiansyah; Putri, Anisya Wittamar; Fitriani, Desnine Ghazalah; Putri, Lingga Satriani; Maulana Rahman, Muhammad Nazwan (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2024)
This study aims to analyze the impact of investment and working capital on profitability at Toko Satria Jaya Cemplang. In an increasingly competitive business environment, particularly in the small and medium-sized enterprises (SMEs) sector, a deep understanding of capital management and investment is crucial. The methods employed in this research include in-depth interviews and direct observations to collect primary data. Data analysis was conducted qualitatively using a thematic analysis approach. The results indicate that efficient investment management and optimal use of working capital significantly contribute to profitability enhancement. This study also identifies the challenges faced by Toko Satria Jaya Cemplang in competing with imported products in digital marketplaces. The findings are expected to provide insights for business actors in formulating better strategies to improve their business performance.